How Achieving the Millennium Development Goals Increases Subjective Well-Being in Developing Nations - Shizuki Fukuda (Sustainability, 2016)
The target date in 2015 for the United Nation’s Millennium Development Goals (MDGs) was reached, and a new period of global goals for the post-2015 is dawning. To assess whether and how regional progress towards achieving the MDGs has contributed to better quality of life in developing nations, we formulated a correlation between various aspects of human development, indicated by MDG indicators, and subjective well-being (SWB), a response to the question of how much people feel happy or satisfied. We demonstrated that national levels of SWB can be explained by the degree of development; poverty reduction is the strongest determinant, and achieving the MDGs is associated with higher SWB levels. Scenario assessment of SWB allowed which domain of development should be improved preferentially in each region to be determined, hence the SWB approach is expected to offer an innovative proxy of human development for the assessment of the Sustainable Development Goals (SDGs).